2014
DOI: 10.1371/journal.pone.0097687
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension in Wild Type Mice and Animals with Genetic Deficit in KCa2.3 and KCa3.1 Channels

Abstract: ObjectiveIn vascular biology, endothelial KCa2.3 and KCa3.1 channels contribute to arterial blood pressure regulation by producing membrane hyperpolarization and smooth muscle relaxation. The role of KCa2.3 and KCa3.1 channels in the pulmonary circulation is not fully established. Using mice with genetically encoded deficit of KCa2.3 and KCa3.1 channels, this study investigated the effect of loss of the channels in hypoxia-induced pulmonary hypertension.Approach and ResultMale wild type and KCa3.1−/−/KCa2.3T/T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 50 publications
1
16
1
Order By: Relevance
“…BKCa channel expression and function has been shown to be elevated in chronic hypoxic mice and PASMCs [27, 28]. In concert with the pulmonary hypertension model, for the first time, we have shown that the BKCa channel and β-subunits are upregulated in remodelled pulmonary arteries obtained by laser-captured microdissection from IPAH patients.…”
Section: Discussionmentioning
confidence: 79%
“…BKCa channel expression and function has been shown to be elevated in chronic hypoxic mice and PASMCs [27, 28]. In concert with the pulmonary hypertension model, for the first time, we have shown that the BKCa channel and β-subunits are upregulated in remodelled pulmonary arteries obtained by laser-captured microdissection from IPAH patients.…”
Section: Discussionmentioning
confidence: 79%
“…In previous studies of K Ca 2.3 T/T mice with and without doxycycline-treatment, only few studies have compared the results with wild type mice 17, 18, 45 , and it can be discussed whether the wild type or the upregulated K Ca 2.3 T/T (−Dox) mice are the correct controls animals to compare the responses with in animals with downregulation of the K Ca 2.3 channels. The K Ca 2.3  T/T channel mice are born with an overexpression of the K Ca 2.3 channel and that affects probably also the vascular structure and heart during the growth of the animals 45 . At 16 Hz stimulation of the cavernous nerve, the erectile responses are less compared to the WT both in the K Ca 2.3 T/T (−Dox) mice and the K Ca 2.3 T/T (+Dox) mice.…”
Section: Discussionmentioning
confidence: 99%
“…K Ca 3.1 −/− and wt mice were derived from our breeding colonies (Si et al ., ; Lambertsen et al ., ; Wandall‐Frostholm et al ., ). All animal protocols or in vitro studies were performed in agreement with the ARRIVE guidelines and approved by the Danish animal care committee (permission 2011/561–2011; Kilkenny et al ., ; McGrath et al ., ).…”
Section: Methodsmentioning
confidence: 97%